Advanced Engineering Informatics - Philosophical and methodological foundations with examples from civil and construction engineering. (November 2020) - Hartmann, Timo; Trappey, Amy
Abstract: We argue that the representation and formalization of complex engineering knowledge is the main aim of inquiries in the scientific field of Advanced Engineering Informatics. We introduce ontology and logic as underlying methods to formalize knowledge. We also suggest that it is important to account for the purpose of engineers and the context they work in while representing and formalizing knowledge. Based on the concepts of ontology, logic, purpose, and context, we discuss different possible research methods and approaches that scholars can use to formalize complex engineering knowledge and to validate whether a specific formalization can support engineers with their complex tasks. On the grounds of this discussion, we suggest that Advanced Engineering research efforts should be conducted in a bottom-up manner closely involving engineering practitioners. We also suggest that researchers make use of social science methods while eliciting knowledge to formalize and while validating their formalized knowledge. Highlights: Advanced Engineering Informatics focuses on engineering knowledge formalization. Ontology and logic as underlying methods for knowledge formalization. Ontology and logic needs to account for engineering purpose and context. Social science influenced methods help to formalize and validate knowledge. Knowledge formalization needs to be a bottom-up activity.